Anomalous radiocarbon ages for foraminifera shells - Broecker, W.; Barker, S.; Clark, E.; Hajdas, I.; Bonani, G. (Paleoceanography, 2006)
The causes for discordant radiocarbon results on multiple species of planktonic foraminifera from high-sedimentation-rate marine sediments are investigated. We have documented two causes for these anomalous results. One is the addition of secondary radiocarbon for which we have, to date, only one firm example. It involves an opal-rich sediment. The other is the incorporation of reworked material. Again, we have, to date, only one firm example. It involves a rapidly deposited ocean margin sediment. However, we have three other examples where reworking is the most likely explanation. On the basis of this study it is our conclusion that, where precise radiocarbon dating of high-deposition-rate marine sediment is required, a prerequisite is to demonstrate that concordant ages can be obtained on pairs of fragile and robust planktic shells. For sediment rich in opal, it is advisable to check for secondary calcite by comparing ages obtained on acid-leached samples with those on unleached samples.
id: 980; 041JB Times Cited:7 Cited References Count:7